(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Migraine is the most common neurological condition in the world affecting about 1 in 10 people. It is 3 times more common in women. Several studies suggest an association of migraine with the body mass index, blood group and comorbidities. The aim of this study is to determine a possible relationship between the prevalence, symptoms, triggers and comorbidities of migraine as well as its association with obesity and blood group. Design A prospective observational study Subject and Methods A total of 204 patients with migraine were included whose age ranged between 18 to 65 years of both gender. The prevalence of migraine and its relation to body mass index and blood group were analyzed. Results The study included 83.82% females and 16.18% males. 36.6% of the included patients have a normal body weight and the study concluded that majority (90%) have O positive blood group. Symptoms are experienced mostly during the attack stage and the major trigger was emotional stress affecting 53% of study population. Conclusion Prevalence of migraine is high among females. Younger age and female sex are other contributory factors as prevalence of migraine. Emotional stress is mediating as the major trigger of migraine and excluding the normal eight subjects, pre-obese patients have higher risk for migraine. The co-morbidities didn’t suggest any apparent relation with migraine, though hypothyroidism was observed in a few populations.